Study on ESD characteristics of T-shape gate GaN HEMT microwave devices - Ni Zhiyuan; Bai Lin; Ling Gang; Bao Cheng; Zhang Junyun (Dianzi Jishu Yingyong, 2025)
The failure mechanisms and influencing factors of Si-based GaN HEMT devices under ESD events were systematically investigated. The study analyzed the failure voltage distribution of the devices under various bias conditions and utilized EMMI to pinpoint abnormal regions responsible for device degradation, followed by micro-area characterization. Furthermore, the impact of key process parameters, such as the geometric dimensions of the T-gate, including gate foot width, gate head width, and total gate width, on the anti-static robustness of the devices was examined. Mechanism analyses were conducted to elucidate these effects. The findings provide valuable insights and practical guidance for optimizing the ESD performance and enhancing the reliability of Si-based GaN HEMT devices.